Long-term evolution of pH and metals (Al, Fe, Mn, U) in pyrite-bearing waste rocks using reactive transport modeling: Dealing with stock and process uncertainties - Sophie Guillon; Pierre L'Hermite; Catherine Beaucaire; Nicolas Seigneur; Martine Leermakers; Benoit Reilé; Vincent Lagneau; Guillaume Kern; Antoine De Amorin; Michael Descostes (Journal of Geochemical Exploration, 2026)

Genome sequencing and multi-stage, blood-feeding, and tissue-specific transcriptome atlas of the Rocky Mountain wood tick provide a critical resource for this vector - Joshua E. Tompkin; Perot Saelao; Justyna Kruczalak; Huiqing Yeo; Pia U. Olafson; Sheina B. Sim; Kennan Oyen; Melissa Kelley; Renee L. Corpuz; Brian Scheffler; Scott M. Geib; Anna K. Childers; et al. (Insect Biochemistry and Molecular Biology, 2026)

Beetle communities in agricultural landscapes: relative influences of climate, landscape, plant communities and agricultural practices - B. Penel; L. Genty; C. Marty; A. Bourdonné; A.-L. Clamens; L. Benoit; L. Soldati; A. Migeon; G.J. Kergoat; J. Haran; G. Fried; C.N. Meynard (Agriculture, Ecosystems & Environment, 2026)

Microbial Ecology of Mixotrophic Chain Elongation: Megasphaera spp. as Drivers of Medium‐Chain Carboxylate Production From H 2 , CO 2 , and Carboxylates - Grégoire B. L. Henry; Julien Tremblay; Benoit A. Stenuit; Patrick A. Gerin (Environmental Microbiology, 2026)
The production of medium‐chain carboxylates (MCC) by mixed culture fermentation of complex organic feedstocks is often constrained by the availability of reducing equivalents. Therefore, mixotrophic fermentation processes, which integrate diverse carbon and reducing equivalents sources, are gaining more attention. However, the microbial communities evolving in such complex environments, where organic and inorganic substrates interact, remain insufficiently understood. To identify the key microorganisms involved in mixotrophic MCC production, two bioreactors were initially fed with brewer's spent grain as organic feedstock and supplemented daily with H 2 and CO 2 as inorganic substrates. Time‐course analyses of net metabolite production rates and microbial community composition identified Megasphaera spp. (likely M. elsdenii and M. hexanoica ) as the main chain elongators in the system. The results suggest that these Megasphaera species metabolize short‐chain carboxylates, H 2 and CO 2 , with potential cross‐feeding interactions with acetogens (likely Clostridium ljungdahlii and Clostridium luticellarii ). The homoacetogenic acetate produced is subsequently elongated, likely by Megasphaera species, using H 2 and CO 2 as electron and carbon sources for production of elongated carboxylates. This study paves the way for the development of MCC production strategies that integrate organic waste valorization with direct CO 2 utilization, using H 2 as an electron donor, a process that aligns with low‐carbon‐footprint technologies.

Soil Invertebrate Body Size Groups and Effect Magnitude Jointly Influence Global Soil CO 2 Emissions - Cheng Liu; Catherine L. Parr; Benoit Guénard; Xiaoyu Cen; Hua Chai; Mingxu Li; Zhiwei Zhong; Shenliang Zhao; Jie Li; Nianpeng He (Global Change Biology, 2026)
Soil invertebrates represent vital components of belowground biodiversity and play pivotal roles in regulating key carbon (C) cycling processes, particularly soil respiration. Despite the recognised effects of invertebrates on soil respiration, previous studies suffer from a major blind spot: a lack of global‐scale interpretations of inferred associations describing how these organisms mediate C release. In this study, we integrated 556 datasets spanning 90 publications to systematically assess the global patterns and inferred associations by which soil invertebrates influence soil respiration. The results revealed that soil invertebrates, on average, enhanced soil respiration by 52%. Across climatic zones, the magnitude of this positive effect tended to decline from tropical to temperate regions. When classified by body size, among the large‐bodied soil invertebrates, ants and termites increased soil respiration by 60% and 62%, respectively, whereas earthworms stimulated it by 47%. In contrast, small‐to‐medium‐bodied soil invertebrates exerted no significant effect. Across ecosystem types, soil invertebrates stimulated soil respiration more strongly in forest ecosystems, with an increase of 55%, compared to a 44% increase in grassland ecosystems. The pathways through which soil invertebrates influence respiration varied markedly among body‐size groups and ecosystem types. Overall, soil invertebrates primarily influenced soil microbial biomass C, fungal biomass and bacterial biomass, as well as soil organic N, soil organic C and soil pH, which in turn were closely associated with soil respiration. These findings underscore the key role of soil invertebrates in influencing soil CO 2 emissions and provide insights essential for improving Earth system models under ongoing climate change.

Role of phthalates in breast cancer initiation, progression and drug rersistance: A scoping review and recommendations - L. Benoit; C. Tomkiewicz; S. Bortoli; A.S. Bats; X. Coumoul; M. Koual (Toxicology Letters, 2025)

Role of viral coinfection in post-pandemic invasive Group A streptococcal infections in adults, a nation-wide cohort study (iGASWISS) - S. Musumeci; A. MacPhail; M. Weisser Rohacek; A. Erba; D. Goldenberger; C. Lang; E. Colin-Benoit; S. L. Leib; P. Sendi; C. Chuard; V. Erard; C. Fournier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Objective During the winter season of 2022–2023, numerous countries experienced a surge in invasive Streptococcus pyogenes (iGAS) infections. The role of viral coinfections in the post-COVID surge has not been elucidated. We report nation-wide data describing clinical presentation, microbiological characteristics, and associations with viral infection in adults during this period. Methods A multicenter retrospective cohort study was conducted across 10 hospitals in Switzerland, including adults (> 16 years old) with iGAS infection from November 2022 to February 2023. Descriptive analysis was performed. A multivariable logistic regression model was fitted to assess the impact of viral coinfection. In addition, genetic analysis was performed in available isolates. Results A total of 194 patients were included, with a median age of 50 years (interquartile range [IQR]: 37–69). 17/194 (8.8%) were immunosuppressed and 40/194 (20.6%) exhibited concomitant viral infections, predominantly Influenza A (21/40, 53%). Illness severity was high: 65/194 (33.5%) of cases necessitated admission to an intensive care unit (ICU), and the 30-day mortality was 4% ( n = 8). Among the available strains for genetic analysis ( n = 48), heterogeneity was found although ST28- emm 1 isolates (also known as M1UK) was predominant (22/48). Conclusion The post-COVID iGAS surge in Switzerland was associated with high levels of morbidity and mortality in immunocompetent adults. M1UK was predominant within the iGAS strains circulating in Switzerland during the study period and viral coinfection was a predictor for ICU admission and mortality.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Skeletal accumulations of the parareptile Procolophon trigoniceps reflect fossorial response to Early Triassic climatic instability across southern Gondwana - Roger M.H. Smith; Frederik P. Wolvaardt; Juan C. Cisneros; Felipe L. Pinheiro; Joseph J. Bevitt; Julien Benoit (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Monolithic TiO2-CeO2 and Pt/TiO2-CeO2@VUKOPOR®A foams in oxidation of dichloromethane and methanol - Ivana Troppová; Lenka Matějová; Kateřina Karásková; Satu Pitkäaho; Vasiliki Papaefthimiou; Benoit Louis; Ondřej Kania; Riitta L. Keiski (Journal of Environmental Chemical Engineering, 2025)

Amino acid analysis using multiple time point hydrolysis and non-linear regression for determination of amino acid profiles and 21-hour correction factors of biological standards, and dairy cattle milk, tissue, rumen microbes, and various feeds - Andres F. Ortega; Joyce L. Marumo; Rebecca Coombe; Alexandria C. Benoit; Deborah A. Ross; Michael E. Van Amburgh (Animal Feed Science and Technology, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Speciation of uranium and radium during the treatment of acidic waters from legacy-mine (Le Cellier, France) - Pascal E. Reiller; Pierre L’Hermite; Valérie Plagnes; Anne Jost; Benoit Reilé; Martine Leermakers; Michaël Descostes (Journal of Environmental Chemical Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

Metabolomic monitoring of chicory during in vitro gastrointestinal digestion and correlation with bioactive properties - Céline L. Pouille; Camille Dugardin; Josette Behra; Melissa Tourret; Roland Molinié; Jean-Xavier Fontaine; David Mathiron; Cécile Palaric; David Gagneul; Rozenn Ravallec; Caroline Rambaud; Jean-Louis Hilbert; et al. (Food Chemistry, 2025)

Modelling the population dynamics of Rift Valley fever virus mosquito vectors in the western Mediterranean Basin - Alex Drouin; Thomas Balenghien; Benoit Durand; Carles Aranda; Amal Bennouna; Ali Bouattour; Said C Boubidi; Annamaria Conte; Sarah Delacour; Maria Goffredo; Oumnia Himmi; Grégory L'Ambert; et al. (Ecological Modelling, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Life history stage effects on alert and flight initiation distances in king penguins (Aptenodytes patagonicus) - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2025)

Scaling up ocean conservation through recognition of key biodiversity areas in the Southern Ocean from multispecies tracking data - Sarah L. Becker; Charlotte Boyd; Jonathan M. Handley; Ben Raymond; Ryan Reisinger; Yan Ropert‐Coudert; Nora Apelgren; Tammy E. Davies; Mary‐Anne Lea; Mercedes Santos; Philip N. Trathan; Anton P. Van de Putte; et al. (Conservation Biology, 2025)
Biodiversity is critical for maintaining ecosystem function but is threatened by increasing anthropogenic pressures. In the Southern Ocean, a highly biologically productive region containing many endemic species, proactive management is urgently needed to mitigate increasing pressures from fishing, climate change, and tourism. Site‐based conservation is one important tool for managing the negative impacts of human activities on ecosystems. The Key Biodiversity Area (KBA) Standard is a standardized framework used to define sites vital for the persistence of global biodiversity based on criteria and quantitative thresholds. We used tracking data from 14 species of Antarctic and subantarctic seabirds and pinnipeds from the publicly available Retrospective Analysis of Antarctic Tracking Data (RAATD) data set to define KBAs for a diverse suite of marine predators. We used track2kba, an R package that supports identification of KBAs from telemetry data through identification of highly used habitat areas and estimates of local abundance within sites. We compared abundance estimates at each site with thresholds for KBA criteria A1, B1, and D1 (related to globally threatened species, individual geographically restricted species, and demographic aggregations, respectively). We identified 30 potential KBAs for 13 species distributed throughout the Southern Ocean that were vital for each individual species, population, and life‐history stage for which they were determined. These areas were identified as highly used by these populations based on observational data and complement the ongoing habitat modeling and bioregionalization work that has been used to prioritize conservation areas in this region. Although further work is needed to identify potential KBAs based on additional current and future data sets, we highlight the benefits of utilizing KBAs as part of a holistic approach to marine conservation, given their significant value as a global conservation tool.

Special Issue on Earth’s Changing Water and Energy Cycle - Benoit Meyssignac; Sonia Seneviratne; Remy Roca; Graeme L. Stephens; Michael Rast (Surveys in Geophysics, 2024)

Legacy nutrients in the Baltic Sea drainage basin: How past practices affect eutrophication management - Bärbel Müller-Karulis; Michelle L. McCrackin; Benoit Dessirier; Bo G. Gustafsson; Christoph Humborg (Journal of Environmental Management, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Combined impact of no-tillage and cover crops on soil carbon stocks and fluxes in maize crops - Nicolas L. Breil; Thierry Lamaze; Vincent Bustillo; Claire-Emmanuelle Marcato-Romain; Benoit Coudert; Solen Queguiner; Nathalie Jarosz-Pellé (Soil and Tillage Research, 2023)

Disentangling the “many-eyes”, “dilution effect”, “selfish herd”, and “distracted prey” hypotheses in shaping alert and flight initiation distance in a colonial seabird - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Data quality control considerations in multivariate environmental monitoring: experience of the French coastal network SOMLIT - Elsa Breton; Nicolas Savoye; Peggy Rimmelin-Maury; Benoit Sautour; Eric Goberville; Arnaud Lheureux; Thierry Cariou; Sophie Ferreira; Hélène Agogué; Samir Alliouane; Fabien Aubert; Sébastien Aubin; et al. (Frontiers in Marine Science, 2023)
Introduction While crucial to ensuring the production of accurate and high-quality data—and to avoid erroneous conclusions—data quality control (QC) in environmental monitoring datasets is still poorly documented. Methods With a focus on annual inter-laboratory comparison (ILC) exercises performed in the context of the French coastal monitoring SOMLIT network, we share here a pragmatic approach to QC, which allows the calculation of systematic and random errors, measurement uncertainty, and individual performance. After an overview of the different QC actions applied to fulfill requirements for quality and competence, we report equipment, accommodation, design of the ILC exercises, and statistical methodology specially adapted to small environmental networks (<20 laboratories) and multivariate datasets. Finally, the expanded uncertainty of measurement for 20 environmental variables routinely measured by SOMLIT from discrete sampling—including Essential Ocean Variables—is provided. Results, Discussion, Conclusion The examination of the temporal variations (2001–2021) in the repeatability, reproducibility, and trueness of the SOMLIT network over time confirms the essential role of ILC exercises as a tool for the continuous improvement of data quality in environmental monitoring datasets.

PERMANOVA testing and Poisson Log-Normal modelling unravel how two traditional cheeses are distinguished through sorting and verbalization tasks - P.-M. Grollemund; L. Lenoir; J. Benoit; C. Chassard; C. Bord (Food Quality and Preference, 2023)

Determinants of sun bear Helarctos malayanus habitat use in Sabah, Malaysian Borneo and its predicted distribution under future forest degradation and loss - Roshan Guharajan; Jesse F. Abrams; Nicola K. Abram; Hong Ye Lim; Gopalasamy Reuben Clements; Nicolas J. Deere; Matthew J. Struebig; Benoit Goossens; Penny C. Gardner; Jedediah F. Brodie; Alys Granados; Shu Woan Teoh; et al. (Biodiversity and Conservation, 2023)

G﻿lobal phylogeography of ridley sea turtles (Lepidochelys spp.): evolution, demography, connectivity, and conservation - Sibelle Torres Vilaça; Anelise Torres Hahn; Eugenia Naro-Maciel; F. Alberto Abreu-Grobois; Brian W. Bowen; Jaqueline C. Castilhos; Claudio Ciofi; Nancy N. FitzSimmons; Michael P. Jensen; Angela Formia; Colin J. Limpus; Chiara Natali; et al. (Conservation Genetics, 2022)
Globally distributed marine taxa are well suited for investigations of biogeographic impacts on genetic diversity, connectivity, and population demography. The sea turtle genus Lepidochelys includes the wide-ranging and abundant olive ridley ( L. olivacea ), and the geographically restricted and ‘Critically Endangered’ Kemp’s ridley ( L. kempii ). To investigate their historical biogeography, we analyzed a large dataset of mitochondrial DNA (mtDNA) sequences from olive (n = 943) and Kemp’s (n = 287) ridleys, and genotyped 15 nuclear microsatellite loci in a global sample of olive ridleys (n = 285). We found that the ridley species split ~ 7.5 million years ago, before the Panama Isthmus closure. The most ancient mitochondrial olive ridley lineage, located in the Indian Ocean, was dated to ~ 2.2 Mya. Both mitochondrial and nuclear markers revealed significant structure for olive ridleys between Atlantic (ATL), East Pacific (EP), and Indo-West Pacific (IWP) areas. However, the divergence of mtDNA clades was very recent (< 1 Mya) with low within- clade diversity, supporting a recurrent extinction-recolonization model for these ocean regions. All data showed that ATL and IWP groups were more closely related than those in the EP, with mtDNA data supporting recent recolonization of the ATL from the IWP. Individual olive ridley dispersal between the ATL, EP, and IN/IWP could be interpreted as more male- than female-biased, and genetic diversity was lowest in the Atlantic Ocean. All populations showed signs of recent expansion, and estimated time frames were concordant with their recent colonization history. Investigating species abundance and distribution changes over time is central to evolutionary biology, and this study provides a historical biogeographic context for marine vertebrate conservation and management.

Oceanic giants dance to atmospheric rhythms: Ephemeral wind‐driven resource tracking by blue whales - John P. Ryan; Kelly J. Benoit‐Bird; William K. Oestreich; Paul Leary; Kevin B. Smith; Chad M. Waluk; David E. Cade; James A. Fahlbusch; Brandon L. Southall; John E. Joseph; Tetyana Margolina; John Calambokidis; et al. (Ecology Letters, 2022)
Trophic transfer of energy through marine food webs is strongly influenced by prey aggregation and its exploitation by predators. Rapid aggregation of some marine fish and crustacean forage species during wind‐driven coastal upwelling has recently been discovered, motivating the hypothesis that predators of these forage species track the upwelling circulation in which prey aggregation occurs. We examine this hypothesis in the central California Current Ecosystem using integrative observations of upwelling dynamics, forage species' aggregation, and blue whale movement. Directional origins of blue whale calls repeatedly tracked upwelling plume circulation when wind‐driven upwelling intensified and aggregation of forage species was heightened. Our findings illustrate a resource tracking strategy by which blue whales may maximize energy gain amid ephemeral foraging opportunities. These findings have implications for the ecology and conservation of diverse predators that are sustained by forage populations whose behaviour is responsive to episodic environmental dynamics.

Genome of elegance coral Catalaphyllia jardinei (Euphylliidae) - Yifei Yu; Wenyan Nong; Wai Lok So; Yichun Xie; Ho Yin Yip; Jasmine Haimovitz; Thomas Swale; David M. Baker; William G. Bendena; Ting Fung Chan; Apple P. Y. Chui; Kwok Fai Lau; et al. (Frontiers in Marine Science, 2022)
Coral reefs are under stress throughout the world. To better understand the molecular mechanisms underlying coral biology and their genomic evolution, here we sequenced the genome and transcriptomes of elegance coral Catalaphyllia jardinei (Euphylliidae). This monotypic genus stony coral is widespread but rare, being found across the Indo-West Pacific, from the northern Indian Ocean, Australia, Philippines, to the South China Sea. Due to its popularity among aquarium hobbyists, it is an overexploited species collected in large quantities from the wild for aquarium trade. The assembled genome is ~ 651.3 Mb in total length and of high physical contiguity with a scaffold N50 size of 28.9 Mb. The gene copy numbers of abiotic stress regulator (heat shock protein family genes) and neuropeptides (GLWamide, GRFamide, PRGamide and HIRamide) are similar to other sequenced anthozoans, and we have also identified the first set of sesquiterpenoid biosynthetic pathway genes in coral. Sequencing of small RNAs allows us to identify 35 microRNAs in C. jardinei and update the number of conserved microRNAs in cnidarians. This study established a foundation for further investigation into the roles of sesquiterpenoids and microRNAs in development of coral and understand their responses to climate change. Due to the easiness to culture C. jardinei in reef tanks and the established resources in this study, we propose this species be adopted as a new laboratory model in environmental and ecological experiments aiming to understand coral biology and responses to environmental stressors.

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Circulating level of Angiopoietin-2 is associated with acute kidney injury in coronavirus disease 2019 (COVID-19) - Brandon Michael Henry; Maria Helena Santos de Oliveira; Isaac Cheruiyot; Justin L. Benoit; David S. Cooper; Giuseppe Lippi; Timothy D. Le Cras; Stefanie W. Benoit (Angiogenesis, 2021)

Cross-tolerance and transcriptional shifts underlying abiotic stress in the seabird tick, Ixodes uriae - Benjamin Davies; Andrew J. Rosendale; Josiah D. Gantz; Richard E. Lee; David L. Denlinger; Joshua B. Benoit (Polar Biology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Strong habitat and weak genetic effects shape the lifetime reproductive success in a wild clownfish population - Océane C. Salles; Glenn R. Almany; Michael L. Berumen; Geoffrey P. Jones; Pablo Saenz‐Agudelo; Maya Srinivasan; Simon R. Thorrold; Benoit Pujol; Serge Planes (Ecology Letters, 2020)
The relative contributions of environmental, maternal and additive genetic factors to the Lifetime reproductive success (LRS) determine whether species can adapt to rapid environmental change. Yet to date, studies quantifying LRS across multiple generations in marine species in the wild are non‐existent. Here we used 10‐year pedigrees resolved for a wild orange clownfish population from Kimbe Island (PNG) and a quantitative genetic linear mixed model approach to quantify the additive genetic, maternal and environmental contributions to variation in LRS for the self‐recruiting portion of the population. We found that the habitat of the breeder, including the anemone species and geographic location, made the greatest contribution to LRS. There were low to negligible contributions of genetic and maternal factors equating with low heritability and evolvability. Our findings imply that our population will be susceptible to short‐term, small‐scale changes in habitat structure and may have limited capacity to adapt to these changes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Seismic properties of gabbroic sections in oceanic core complexes: constraints from seafloor drilling - Donna K. Blackman; Natsue Abe; Richard L. Carlson; Gilles Guerin; Benoit Ildefonse; Amber Kumpf (Marine Geophysical Research, 2019)

The Antarctic mite, Alaskozetes antarcticus, shares bacterial microbiome community membership but not abundance between adults and tritonymphs - Christopher J. Holmes; Emily C. Jennings; J. D. Gantz; Drew Spacht; Austin A. Spangler; David L. Denlinger; Richard E. Lee; Trinity L. Hamilton; Joshua B. Benoit (Polar Biology, 2019)

LRP1 Has a Predominant Role in Production over Clearance of Aβ in a Mouse Model of Alzheimer’s Disease - Bart Van Gool; Steffen E. Storck; Sara M. Reekmans; Benoit Lechat; Philip L. S. M. Gordts; Laurent Pradier; Claus U. Pietrzik; Anton J. M. Roebroek (Molecular Neurobiology, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

Evolution of the latitudinal diversity gradient in the hyperdiverse ant genus Pheidole - Evan P. Economo; Jen‐Pan Huang; Georg Fischer; Eli M. Sarnat; Nitish Narula; Milan Janda; Benoit Guénard; John T. Longino; L. Lacey Knowles (Global Ecology and Biogeography, 2019)
Aim The latitudinal diversity gradient is the dominant geographic pattern of life on Earth, but a consensus understanding of its origins has remained elusive. The analysis of recently diverged, hyper‐rich invertebrate groups provides an opportunity to investigate latitudinal patterns with the statistical power of large trees while minimizing potentially confounding variation in ecology and history. Here, we synthesize global phylogenetic and macroecological data on a hyperdiverse (> 1,100 species) ant radiation, Pheidole and test predictions of three general explanations for the latitudinal gradient: variation in diversification rates, tropical conservatism and ecological regulation. Location Global. Time period The past 35 million years. Major taxa studied The hyperdiverse ant genus Pheidole Westwood. Methods We assembled geographic data for 1,499 species and morphospecies, and inferred a dated phylogeny for 449 species of Pheidole , including 167 species newly sequenced for this study. We tested for correlations between diversification rate and latitude with Bayesian analysis of macroevolutionary mixtures (BAMM), hidden state speciation and extinction (HiSSE), geographic state speciation and extinction (GeoSSE), and a non‐parametric method (FiSSE), evaluated evidence for richness steady state, and examined patterns of diversification as Pheidole spread around the globe. Results There was no evidence of systematic variation of net diversification rates with latitude across any of the methods. We found that Pheidole diversification occurred in bursts when new continents were colonized, followed by a slowdown in each region, but there is no evidence richness has saturated at an equilibrium in any region. Additionally, we found latitudinal affinity is moderately conserved with a Neotropical ancestor and simulations show that phylogenetic inertia alone is sufficient to produce the gradient pattern. Main conclusions Our results provide no evidence that diversification rates vary systematically with latitude. Richness is far from steady state in each region, contrary to the ecological regulation hypothesis, although there is evidence that ecological opportunity promotes diversification after colonization of new areas. The fact that niche conservatism is strong enough to produce the gradient pattern is in accord with the tropical conservatism hypothesis. Overall, these results shed light on the mechanisms underlying the emergence of the diversity gradient within the past 34 million years, complementing recent work on deeper time‐scales, and more generally contribute toward much‐needed invertebrate perspective on global biodiversity dynamics.

Sex- and developmental-specific transcriptomic analyses of the Antarctic mite, Alaskozetes antarcticus, reveal transcriptional shifts underlying oribatid mite reproduction - Hannah E. Meibers; Geoffrey Finch; Robert T. Gregg; Sierra Glenn; Keavash D. Assani; Emily C. Jennings; Benjamin Davies; Andrew J. Rosendale; Christopher J. Holmes; J. D. Gantz; Drew E. Spacht; Richard E. Lee; et al. (Polar Biology, 2019)

Survival strategies of a frugivore, the sun bear, in a forest-oil palm landscape - Roshan Guharajan; Todd W. Arnold; Gilmoore Bolongon; Grace H. Dibden; Nicola K. Abram; Shu Woan Teoh; Mohd Azzumar Magguna; Benoit Goossens; Siew Te Wong; Senthilvel K. S. S. Nathan; David L. Garshelis (Biodiversity and Conservation, 2018)

Inbreeding tolerance as a pre‐adapted trait for invasion success in the invasive ant Brachyponera chinensis - Pierre‐André Eyer; Kenji Matsuura; Edward L. Vargo; Kazuya Kobayashi; Toshihisa Yashiro; Wataru Suehiro; Chihiro Himuro; Tomoyuki Yokoi; Benoit Guénard; Robert R. Dunn; Kazuki Tsuji (Molecular Ecology, 2018)
Identifying traits that facilitate species introductions and successful invasions of ecosystems represents a key issue in ecology. Following their establishment into new environments, many non‐native species exhibit phenotypic plasticity with post‐introduction changes in behaviour, morphology or life history traits that allow them to overcome the presumed loss of genetic diversity resulting in inbreeding and reduced adaptive potential. Here, we present a unique strategy in the invasive ant Brachyponera chinensis (Emery) , in which inbreeding tolerance is a pre‐adapted trait for invasion success, allowing this ant to cope with genetic depletion following a genetic bottleneck. We report for the first time that inbreeding is not a consequence of the founder effect following introduction, but it is due to mating between sister queens and their brothers that pre‐exists in native populations which may have helped it circumvent the cost of invasion. We show that a genetic bottleneck does not affect the genetic diversity or the level of heterozygosity within colonies and suggest that generations of sib‐mating in native populations may have reduced inbreeding depression through purifying selection of deleterious alleles. This work highlights how a unique life history may pre‐adapt some species for biological invasions.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Phylogeography, evolutionary history and effects of glaciations in a species ( Zootoca vivipara ) inhabiting multiple biogeographic regions - Jose L. Horreo; Maria L. Pelaez; Teresa Suárez; Merel C. Breedveld; Benoit Heulin; Yann Surget‐Groba; Tuula A. Oksanen; Patrick S. Fitze (Journal of Biogeography, 2018)
Aim During glaciations, the distribution of temperate species inhabiting the Northern Hemisphere generally contracts into southern refugia; and in boreo‐alpine species of the Northern Hemisphere, expansion from Northern refugia is the general rule. Little is known about the drivers explaining vast distributions of species inhabiting multiple biogeographic regions (major biogeographic regions defined by the European Environmental Agency). Here we investigate the fine‐scale phylogeography and evolutionary history of the Eurasian common lizard ( Zootoca vivipara ), the terrestrial reptile with the world's widest and highest latitudinal distribution, that inhabits multiple biogeographic regions. Location Eurasia. Methods We generated the largest molecular dataset to date of Z. vivipara , ran phylogenetic analyses, reconstructed its evolutionary history, determined the location of glacial refuges and reconstructed ancestral biogeographic regions. Results The phylogenetic analyses revealed a complex evolutionary history, driven by expansions and contractions of the distribution due to glacials and interglacials, and the colonization of new biogeographic regions by all lineages of Z. vivipara . Many glacial refugia were detected, most were located close to the southern limit of the Last Glacial Maximum. Two subclades recolonized large areas covered by permafrost during the last glaciation: namely, Western and Northern Europe and North‐Eastern Europe and Asia. Main conclusions In Z. vivipara, most of the glacial refugia were located in the South of their current distribution. Previous studies suggested the existence of Northern refuges, but the species' inability to overwinter on permafrost and the lack of genetic support suggest that the presence of a refugia in the north of the Alps is unlikely. This species currently inhabits boreo‐alpine climates and retracted during previous glaciations into southern refugia, as temperate species. Two clades exhibited enormous geographic expansion that started from two distinct glacial refugia. These phylogeographic patterns were highly congruent with those of Vipera berus . Together they suggest that glacial retraction, the location of the refugia and absence of competition may have promoted the enormous geographic expansion of two clades.

Correction to: Anaphylactoid Reactions to Intravenous N-Acetylcysteine during Treatment for Acetaminophen Poisoning - Mark Yarema; Puja Chopra; Marco L. A. Sivilotti; David Johnson; Alberto Nettel-Aguirre; Benoit Bailey; Charlemaigne Victorino; Sophie Gosselin; Roy Purssell; Margaret Thompson; Daniel Spyker; Barry Rumack (Journal of Medical Toxicology, 2018)

Anaphylactoid Reactions to Intravenous N-Acetylcysteine during Treatment for Acetaminophen Poisoning - Mark Yarema; Puja Chopra; Marco L. A. Sivilotti; David Johnson; Alberto Nettel-Aguirre; Benoit Bailey; Charlemaigne Victorino; Sophie Gosselin; Roy Purssell; Margaret Thompson; Daniel Spyker; Barry Rumack (Journal of Medical Toxicology, 2018)

Prey in oceanic sound scattering layers organize to get a little help from their friends - Kelly J. Benoit‐Bird; Mark A. Moline; Brandon L. Southall (Limnology and Oceanography, 2017)
Group formation in animals is a widespread phenomenon driven by food acquisition, reproduction, and defense. Life in the ocean is characteristically aggregated into horizontally extensive layers as a result of strong vertical gradients in the environment. Each day, animals in high biomass aggregations called “deep scattering layers” migrate vertically, comprising the largest net animal movement on earth. This movement is commonly thought of as a predator avoidance tactic, however, the aggregation of animals into layers has been viewed as an incidental outcome of similar responses by many individuals to the risk of visual predation coupled with the location of resources including food and oxygen rather than active, socially mediated congregation for defense purposes. Here, using a newly adapted autonomous vehicle to measure individual characteristics, we provide the first measures of the internal layer structure, demonstrating that these features are made up of many topologically scaled, mono‐specific aggregations, or “schools” rather than an indiscriminate mix of sizes and species. Schools responded to predators using behavior much like flash compression while neighboring aggregations increased their spacing to maintain coherent layers. Rather than simply an incidental outcome, the formation of layers of life in the sea is a highly organized process driven, at least in part, by biotic pressures for cohesion with broad adaptive significance for the myriad species that inhabit these ubiquitous features. These observations highlight the range of spatial scales we must examine in order to understand the strong impacts these high‐biomass layers have on ecological and biogeochemical processes in the sea.

Nitro-Triarylmethyl Radical as Dual Oxygen and Superoxide Probe - Benoit Driesschaert; Andrey A. Bobko; Valery V. Khramtsov; Jay L. Zweier (Cell Biochemistry and Biophysics, 2017)

Pedigree Reconstruction with Genome-Wide Markers in Potato - Jeffrey B. Endelman; Cari A. Schmitz Carley; David S. Douches; Joseph J. Coombs; Benoit Bizimungu; Walter S. De Jong; Kathleen G. Haynes; David G. Holm; J. Creighton Miller; Richard G. Novy; Jiwan P. Palta; David L. Parish; et al. (American Journal of Potato Research, 2017)

Consistency in coral skeletal amino acid composition offshore of Palau in the western Pacific warm pool indicates no impact of decadal variability in nitricline depth on primary productivity - Branwen Williams; Benoit Thibodeau; Yoshito Chikaraishi; Naohiko Ohkouchi; Andrew Walnum; Andréa G. Grottoli; Patrick L. Colin (Limnology and Oceanography, 2017)
The depth of the thermocline and associated nitricline in the western Pacific warm pool (WPWP) vary over time in response to changes in larger ocean‐atmosphere climate patterns. A shoaling of the nitricline in the WPWP brings nitrate‐rich seawater ( > 4 μ mol kg −1 ) above the base of the euphotic zone, stimulating primary productivity. Here, we test if decadal variability in the nitricline depth is driving changes in regional primary productivity and source nitrate dynamics. We use the nitrogen isotopic composition (δ 15 N) of amino acids in the skeleton of a proteinaceous coral collected from the base of the euphotic zone in the WPWP. In proteinaceous corals, as in most organic life, the δ 15 N of phenylalanine matches that of the ambient nitrate while the δ 15 N of trophic amino acids reflect subsequent trophic transfer of the nitrogen prior to incorporation into the coral's food, suspended particulate organic matter. Consistency of the trophic position of the coral calculated from the δ 15 N composition of the coral skeletal amino acids over its 56 yr lifespan suggest that decadal variability in nitricline depth and subsequent shifts in nitrate availability to the euphotic zone have not impacted primary productivity offshore of Palau in the WPWP. This is important when considering the current external forcing of Pacific Ocean climate patterns and the resulting impacts on the global carbon cycle in the Palau region of the WPWP.

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Observed volatilization fluxes of S-metolachlor and benoxacor applied on soil with and without crop residues - C. Bedos; L. Alletto; B. Durand; O. Fanucci; A. Brut; M. Bourdat-Deschamps; S. Giuliano; B. Loubet; E. Ceschia; P. Benoit (Environmental Science and Pollution Research, 2017)

How the truffle got its mate: insights from genetic structure in spontaneous and planted Mediterranean populations of Tuber melanosporum - E. Taschen; F. Rousset; M. Sauve; L. Benoit; M.‐P. Dubois; F. Richard; M.‐A. Selosse (Molecular Ecology, 2016)
The life cycles and dispersal of edible fungi are still poorly known, thus limiting our understanding of their evolution and domestication. The prized Tuber melanosporum produces fruitbodies (fleshy organs where meiospores mature) gathered in natural, spontaneously inoculated forests or harvested in plantations of nursery‐inoculated trees. Yet, how fruitbodies are formed remains unclear, thus limiting yields, and how current domestication attempts affect population genetic structure is overlooked. Fruitbodies result from mating between two haploid individuals: the maternal parent forms the flesh and the meiospores, while the paternal parent only contributes to the meiospores. We analyzed the genetic diversity of T. melanosporum comparatively in spontaneous forests vs. plantations, using SSR polymorphism of 950 samples from South‐East France. All populations displayed strong genetic isolation by distance at the metric scale, possibly due to animal dispersal, meiospore persistence in soil, and/or exclusion of unrelated individuals by vegetative incompatibility. High inbreeding was consistently found, suggesting that parents often develop from meiospores produced by the same fruitbody. Unlike maternal genotypes, paternal mycelia contributed to few fruitbodies each, did not persist over years, and were undetectable on tree mycorrhizae. Thus, we postulate that germlings from the soil spore bank act as paternal partners. Paternal genetic diversity and outbreeding were higher in plantations than in spontaneous truffle‐grounds, perhaps because truffle growers disperse fruitbodies to maintain inoculation in plantations. However, planted and spontaneous populations were not genetically isolated, so that T. melanosporum illustrates an early step of domestication where genetic structure remains little affected.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

Benchmarks for multicomponent reactive transport across a cement/clay interface - Nicolas C. M. Marty; Olivier Bildstein; Philippe Blanc; Francis Claret; Benoit Cochepin; Eric C. Gaucher; Diederik Jacques; Jean-Eric Lartigue; Sanheng Liu; K. Ulrich Mayer; Johannes C. L. Meeussen; Isabelle Munier; et al. (Computational Geosciences, 2015)

Influence of Amazonian deforestation on the future evolution of regional surface fluxes, circulation, surface temperature and precipitation - Quentin Lejeune; Edouard L. Davin; Benoit P. Guillod; Sonia I. Seneviratne (Climate Dynamics, 2015)

Ground cover species selection to manage common ragweed (Ambrosia artemisiifolia L.) in roadside edge of highway - Jichul Bae; Chaeho Byun; Alan K. Watson; Diane L. Benoit (Plant Ecology, 2015)

Emerging roles of aquaporins in relation to the physiology of blood-feeding arthropods - Joshua B. Benoit; Immo A. Hansen; Elise M. Szuter; Lisa L. Drake; Denielle L. Burnett; Geoffrey M. Attardo (Journal of Comparative Physiology B, 2014)

Targeting VEGFR1 on endothelial progenitors modulates their differentiation potential - Clément d’Audigier; Benoit Gautier; Alexis Yon; Jean-Meidi Alili; Coralie L. Guérin; Solène M. Evrard; Anne Godier; Skerdi Haviari; Marie Reille-Serroussi; Florent Huguenot; Blandine Dizier; Nicolas Inguimbert; et al. (Angiogenesis, 2014)

Stratification and mixing regimes in biological thin layers over the Mid‐Atlantic Bight - E. L. Shroyer; K. J. Benoit-Bird,; J. D. Nash; J. N. Moum (Limnology and Oceanography, 2014)
We use density and microstructure data to characterize the properties and physical setting of optical thin layers observed over the New Jersey shelf in the summer of 2006. Layers were differentiated into two types by their vertical position in the water column, fluorescence intensity, and possibly community composition or cell condition as indicated by the measured differences in the ratio of fluorescence to optical backscatter. Both layer types were associated with gradients in stratification; but, the turbulent mixing environment for the two layer types differed significantly. Shallow layers were located within the pycnocline near the maximum stratification and were exposed to strong turbulence within the surface mixed layer. Consequently, turbulent mixing of buoyancy may have been a key factor in maintaining shallow layers. In contrast, relatively weak density gradients and mixing indicate that turbulent processes may have been less critical for deep layers, which were located at the base of the pycnocline. More generally, both shallow and deep layers were geographically located in regions of low median and high mean turbulent kinetic energy dissipation, i.e., regions of rare yet intense mixing events. This work highlights the need to understand the detailed statistics of mixing at time and vertical scales relevant to thin layers, and more specifically, the need to discern the time history of mixing of the fluid that composes layers.

Evolutionary history of almond tree domestication in the M editerranean basin - M. Delplancke; N. Alvarez; L. Benoit; A. Espíndola; H. I Joly; S. Neuenschwander; N. Arrigo (Molecular Ecology, 2013)
Genetic diversity of contemporary domesticated species is shaped by both natural and human‐driven processes. However, until now, little is known about how domestication has imprinted the variation of fruit tree species. In this study, we reconstruct the recent evolutionary history of the domesticated almond tree, Prunus dulcis , around the Mediterranean basin, using a combination of nuclear and chloroplast microsatellites [i.e. simple sequence repeat ( SSR s)] to investigate patterns of genetic diversity. Whereas conservative chloroplast SSR s show a widespread haplotype and rare locally distributed variants, nuclear SSR s show a pattern of isolation by distance with clines of diversity from the East to the West of the Mediterranean basin, while Bayesian genetic clustering reveals a substantial longitudinal genetic structure. Both kinds of markers thus support a single domestication event, in the eastern side of the Mediterranean basin. In addition, model‐based estimation of the timing of genetic divergence among those clusters is estimated sometime during the Holocene, a result that is compatible with human‐mediated dispersal of almond tree out of its centre of origin. Still, the detection of region‐specific alleles suggests that gene flow from relictual wild preglacial populations (in North Africa) or from wild counterparts (in the Near East) could account for a fraction of the diversity observed.

Impact of soil map specifications for European climate simulations - Benoit P. Guillod; Edouard L. Davin; Christine Kündig; Gerhard Smiatek; Sonia I. Seneviratne (Climate Dynamics, 2013)

Extreme Conservation of the psaA/psaB Intercistronic Spacer Reveals a Translational Motif Coincident with the Evolution of Land Plants - Elena L. Peredo; Donald H. Les; Ursula M. King; Lori K. Benoit (Journal of Molecular Evolution, 2012)

Biodegradation of mono-hydroxylated PCBs by Burkholderia xenovorans - Rouzbeh Tehrani; Monica M. Lyv; Rashid Kaveh; Jerald L. Schnoor; Benoit Aken (Biotechnology Letters, 2012)

Disruption of ant-seed dispersal mutualisms by the invasive Asian needle ant (Pachycondyla chinensis) - Mariano A. Rodriguez-Cabal; Katharine L. Stuble; Benoit Guénard; Robert R. Dunn; Nathan J. Sanders (Biological Invasions, 2012)

Genetic structure in a dynamic baboon hybrid zone corroborates behavioural observations in a hybrid population - M. J. E. CHARPENTIER; M. C. FONTAINE; E. CHEREL; J. P. RENOULT; T. JENKINS; L. BENOIT; N. BARTHÈS; S. C. ALBERTS; J. TUNG (Molecular Ecology, 2012)
Behaviour and genetic structure are intimately related: mating patterns and patterns of movement between groups or populations influence the movement of genetic variation across the landscape and from one generation to the next. In hybrid zones, the behaviour of the hybridizing taxa can also impact the incidence and outcome of hybridization events. Hybridization between yellow baboons and anubis baboons has been well documented in the Amboseli basin of Kenya, where more anubis‐like individuals tend to experience maturational and reproductive advantages. However, it is unknown whether these advantages are reflected in the genetic structure of populations surrounding this area. Here, we used microsatellite genotype data to evaluate the structure and composition of baboon populations in southern Kenya. Our results indicate that, unlike for mitochondrial DNA, microsatellite‐based measures of genetic structure concord with phenotypically based taxonomic distinctions and that the currently active hybrid zone is relatively narrow. Isolation with migration analysis revealed asymmetric gene flow in this region from anubis populations into yellow populations, in support of the anubis‐biased phenotypic advantages observed in Amboseli. Populations that are primarily yellow but that receive anubis gene flow exhibit higher levels of genetic diversity than yellow populations far from the introgression front. Our results support previous work that indicates a long history of hybridization and introgression among East African baboons. Specifically, it suggests that anubis baboons are in the process of gradual range expansion into the range of yellow baboons, a pattern potentially explained by behavioural and life history advantages that correlate with anubis ancestry.

Balancing Risk and Costs to Optimize the Clinical Supply Chain—A Step Beyond Simulation - Chedia Abdelkafi; Benoît H. L. Beck; Benoit David; Cédric Druck; Mitchell Horoho (Journal of Pharmaceutical Innovation, 2009)

Nocturnal light and lunar cycle effects on diel migration of micronekton - Kelly J. Benoit-Bird; Whitlow W. L. Au; Daniel W. Wisdoma (Limnology and Oceanography, 2009)
The roles of nocturnal light and lunar phase in the diel migration of micronekton from a nearshore scattering layer were examined. Migration patterns were measured over six complete lunar cycles using moored upward‐looking echosounders while nocturnal surface irradiance was recorded. We hypothesized that animals would remain at a constant isolume at night despite changes in nocturnal illumination between nights. The scattering layer migrated closer to the surface during dark nights than during well‐lit ones. However, this movement was not enough to compensate for observed changes in light, and at night animals often remained at light levels higher than they experience at depth during the day. Light and lunar cycle were not completely coupled, allowing separation of the light and lunar phases. Contrary to the initial hypothesis, lunar phase accounted for substantially more of the variability in layer migration than surface irradiance, showing strong effects on the scattering layer’s depth and animal density within the layer. Changes in layer depth and animal density were amplified a small amount by variations in light level but were minimized by the seafloor in shallow areas. The horizontal component of the scattering layer’s migration was also affected by lunar phase, with animals remaining further offshore in deeper waters during nights near and during the full moon, even when these were not the nights with the highest light levels. These results suggest that moonlight may be a cue for an endogenous lunar rhythm in the process of diel migration rather than a direct cause.

Dehydration, rehydration, and overhydration alter patterns of gene expression in the Antarctic midge, Belgica antarctica - Giancarlo Lopez-Martinez; Joshua B. Benoit; Joseph P. Rinehart; Michael A. Elnitsky; Richard E. Lee; David L. Denlinger (Journal of Comparative Physiology B, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Antarctic Collembolans Use Chemical Signals to Promote Aggregation and Egg Laying - J. B. Benoit; M. A. Elnitsky; G. G. Schulte; R. E. Lee; D. L. Denlinger (Journal of Insect Behavior, 2009)

The seabird tick, Ixodes uriae, uses uric acid in penguin guano as a kairomone and guanine in tick feces as an assembly pheromone on the Antarctic Peninsula - Joshua B. Benoit; Giancarlo Lopez-Martinez; Seth A. Philips; Michael A. Elnitsky; Jay A. Yoder; Richard E. Lee; David L. Denlinger (Polar Biology, 2008)

Extremely large aggregations of collembolan eggs on Humble Island, Antarctica: a response to early seasonal warming? - Glen G. Schulte; Michael A. Elnitsky; Joshua B. Benoit; David L. Denlinger; Richard E. Lee (Polar Biology, 2008)

Adaptations for the maintenance of water balance by three species of Antarctic mites - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Polar Biology, 2008)

Nickel-binding and accessory proteins facilitating Ni-enzyme maturation in Helicobacter pylori - Robert J. Maier; Stéphane L. Benoit; Susmitha Seshadri (BioMetals, 2007)

Habitat requirements of the seabird tick, Ixodes uriae (Acari: Ixodidae), from the Antarctic Peninsula in relation to water balance characteristics of eggs, nonfed and engorged stages - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Journal of Comparative Physiology B, 2007)

The Association Between Cigarette Smoking and Colorectal Polyp Recurrence (United States) - Electra D. Paskett; Katherine W. Reeves; Benoit Pineau; Paul S. Albert; Bette Caan; Marsha Hasson; Frank Iber; James Walter Kikendall; Peter Lance; Moshe Shike; Martha L. Slattery; Joel Weissfeld; et al. (Cancer Causes & Control, 2005)

Prey dynamics affect foraging by a pelagic predator (Stenella longirostris) over a range of spatial and temporal scales - Kelly J. Benoit-Bird; Whitlow W. L. Au (Behavioral Ecology and Sociobiology, 2003)

Fertile Homozygous Transgenic Mice Expressing a Functional Truncated Herpes Simplex Thymidine Kinase ΔTK Gene - Jose L. Cohen; Olivier Boyer; Benoit Salamon; Rosine Onclercq; Daniele Depetris; Laurence Lejeune; Vanessa Dubus-Bonnet; Sylvie Bruel; Frederic Charlotte; Marie-Genevieve Mattei; David Klatzmann (Transgenic Research, 1998)

Accuracy of pulse oximetry during intense exercise under severe hypoxic conditions - H. Benoit; F. Costes; L. Feasson; J. R. Lacour; F. Roche; C. Denis; A. Geyssant; J. C. Barthlmy (European Journal of Applied Physiology, 1997)

Effects of fertilizer on insecticides adsorption and biodegradation in crop soils - J. Rouchaud; A. Thirion; A. Wauters; F. Van de Steene; F. Benoit; N. Ceustermans; J. Gillet; S. Marchand; L. Vanparys (Archives of Environmental Contamination and Toxicology, 1996)